"Is something amiss?" Investigating individuals' competence in estimating swarm degradation. (3rd September 2022) - Capiola, August; Hamdan, Izz aldin; Fox, Elizabeth L.; Lyons, Joseph B.; Sycara, Katia; Lewis, Michael
Abstract: Robotic swarms comprise component assets operating via local control algorithms which emulate natural swarming behaviors. Scientists are beginning to focus on the human-centered topic of human-swarm interaction. In a novel within-subjects design, we followed this comparatively nascent focus and investigated whether people can detect swarm degradations in assets flocking via consensus, their accuracy in estimating those degradations, and their confidence in those estimates. We also assessed open-ended responses to shed light on the strategies people may use to detect swarm degradations. Participants were recruited online and viewed 21 randomized simulations, each 30 seconds in duration with varying proportions of asset degradation. Results showed that the proportion of asset degradation did have an effect on the aforementioned criteria. Qualitative themes showed preliminary evidence that participants used common strategies to detect the time and degree of swarm degradation. However, we did not find evidence of a linear effect of the degradation manipulation on criteria of interest, which did not support our expectations. We discuss limitations and future research perspectives in detail, which we believe provide fodder for future work to investigate human-swarm interaction at a more granular level.